2019
DOI: 10.3390/app9235109
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Self-Compacting Concrete Strength with Non-Destructive Tests for Concrete Structures

Abstract: Self-compacting concrete (SCC) shows to have some specificities when compared to normal vibrated concrete (NVC), namely higher cement paste dosage and smaller volume of coarse aggregates. In addition, the maximum size of coarse aggregates is also reduced in SCC to prevent blocking effect. Such specificities are likely to affect the results of non-destructive tests when compared to those obtained in NVC with similar compressive strength and materials. This study evaluates the applicability of some non-destructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…SCC is characterized by a large content of fines and water [48] and therefore a large proportion of cement paste [32] to achieve proper flowability. The accuracy of non-destructive testing in this particular material, has been demonstrated in some studies [30,47]. Their main conclusion was that the pre-established ratios between compressive strength and the indirect measures, suitable for conventional concretes, were not applicable.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…SCC is characterized by a large content of fines and water [48] and therefore a large proportion of cement paste [32] to achieve proper flowability. The accuracy of non-destructive testing in this particular material, has been demonstrated in some studies [30,47]. Their main conclusion was that the pre-established ratios between compressive strength and the indirect measures, suitable for conventional concretes, were not applicable.…”
Section: Introductionmentioning
confidence: 91%
“…Very early [18] and more recent studies [30] have shown that an increase in the hardened density of concrete facilitates the propagation of ultrasonic pulses. In this study, the necessary reduction of the coarse aggregate content to obtain an SF3 slump-flow class resulted in a lower number of discontinuities within the concrete matrix, which affected this relationship [8].…”
Section: Relationship Between Upv and Densitymentioning
confidence: 99%
See 2 more Smart Citations
“…These aspects are important to fulfill many architectural requirements. In [9], the applicability of non-destructive tests to estimate the compressive strength of self-compacting concrete was studied and useful correlations were presented for practice. Additionally, the performance of structural members in existing structures may have to be evaluated in light of current codes of practice.…”
mentioning
confidence: 99%